HLA-DRB10401 and HLA-DRB10408 Are Strongly Associated with the Development of Antibodies against Interferon-β Therapy in Multiple Sclerosis - HOFFMANN, Steve; CEPOK, Sabine; HEMMER, Bernhard; GRUMMEL, Verena; LEHMANN-HORN, Klaus; HACKERMUELLER, Jörg; STADLER, Peter F; HARTUNG, Hans-Peter; BERTHELE, Achim; DEISENHAMMER, Florian; WASMUTH, Ralf (American journal of human genetics, 2008)
The formation of antibodies to interferon-beta (IFN-beta), a protein-based disease-modifying agent for multiple sclerosis (MS), is a problem in clinical practice. These antibodies may neutralize the biological effects of the protein drug, potentially decreasing its therapeutic effects. By high-resolution HLA class I and II typing we identified two HLA class II alleles associated with the development of antibodies to IFN-beta. In two independent continuous and binary-trait association studies, HLA-DRB1*0401 and HLA-DRB1*0408 (odds ratio: 5.15)--but not other HLA alleles--were strongly associated with the development of binding and neutralizing antibodies to IFN-beta. The associated HLA-DRB1*04 alleles differ from nonassociated HLA-DRB1*04 alleles by a glycine-to-valine substitution in position 86 of the epitope-binding alpha-helix of the HLA class II molecule. The peptide-binding motif of HLA-DRB1*0401 and *0408 might promote binding and presentation of an immunogenic peptide, which may eventually break T cell tolerance and facilitate antibody development to IFN-beta. In summary, we identified genetic factors determining the immunogenicity of IFN-beta, a protein-based disease-modifying agent for the treatment of MS.